ORIENTAÇÕES PARA CONDUTA EM CASO DE ACIDENTE COM MATERIAL BIOLÓGICO EM LABORATÓRIOS CLÍNICOS - Heck, Ritiele; Girardi, Camila E.; Ott, Joice N.; Pletsch, Marilei U. (Salão do Conhecimento, 2013)
Resumo